Sumbangan Izz al-Din Ibn Abd Salam (m. 660H) dalam Perkembangan Sejarah dan Tamadun Islam : Contribution of Izz al-Din Ibn Abd Salam (d. 660H) in the Development of Islamic History and Civilization - Syed Jaafar, Syed Mohd Jeffri; Man, Sa’adan; Pauzi, Norhidayah; Jamaluddin, Mohd Hafiz; Harun, Muhammad Safwan (Journal of Al-Tamaddun, 2024)
Izz al-Din Ibn Abd Salam was one of the most significant figures in the history of Islamic development, particularly in the field of Islamic jurisprudence. His firmness and unwavering principles earned him great respect from both leaders and society, to the extent that he was honoured with titles such as al-Sultan al-Ulama and al-ba’i al-Umara. His contributions to religion and society were so profound that he was appointed as a mufti in two different kingdoms. Despite his influence, research reveals that discussions regarding the factors that contributed to his outstanding prominence remain scarce. This paper aims to examine the factors that shaped the character and prominence of Izz al-Din Ibn Abd Salam throughout his life. The study adopts a qualitative research methodology, gathering data through literature review and analysing it using inductive, deductive, and thematic methods. The research finds that Izz al-Din Ibn Abd Salam was a man of strong principles and firm in defending his views, as evidenced by his fatwas, which were immune to influence by individuals with vested interests. Various factors influenced his distinguished stature, including his scholarly knowledge, socio-political environment, societal influences, and his steadfast adherence to religious beliefs.